Evaluation of design criteria for inflow and infiltration in sewerage system - Samion, Mohd. Kamarul Huda (2006)
The main problem in the sewer pipe is when there are occurences of inflow and infiltration in the sewerage system. It will increase the wastewater flow quantity in the sewerage system itself. Therefore, the rate of inflow and infiltration must be determined, especially for the sewer pipes that is more then 10 years of age. The objectives of this study are to evaluate the rate of inflow and infiltration in sewer pipes, and to evaluate the peak flow factor and characteristics of domestic wastewater in the sewerage systems. The scope of this study involves wastewater flow measurement in residential areas at Putrajaya,Wilayah Persekutuan and Skudai, Johor Bahru, Johor that up to a total of 80000 population equivalent. The wastewater flow is measured by using flowmeter model ISCO 4250, while the automatic rain gauge is used to measure the rainfall intensity. The results of the study indicate a higher rate of inflow and infiltration than the allowable infiltration rate value by Malaysian Standard. Meanwhile, the actual peak flow factor value is lower then the design peak flow factor value. Rainfall events will increase the wastewater quantity and also inflow and infiltration rates in the sewerage system.